Yield of mycobacteriological study in diagnosis of pleural tuberculosis among Human immune deficiency virus-infected patients. (December 2016) - Marjani, Majid; Yousefzadeh, Amir; Tabarsi, Payam; Moniri, Afshin; Akbar Velayati, Ali
Abstract: Background: Pleural tuberculosis (TB) is common among HIV-infected patients. In the absence of HIV infection, the yield of mycobacteriological study is low and usually invasive procedures, including pleural fluid analysis and pleural biopsy, are necessary. The present study aimed to determine the yield of mycobacteriological study of sputum and pleural fluid among HIV-infected patients. Methods: This retrospective case–control study involved HIV-positive and HIV-negative patients with new pleural TB admitted to the National Research Institute of Tuberculosis and Lung Disease, Tehran, Iran, for 5 years. The results of sputum and pleural fluid smear for acid-fast bacilli (AFB) and mycobacterium culture were extracted and compared between the two groups. Results: In the study period, 343 patients were admitted due to pleural TB, of which 42 were HIV-positive patients. We randomly selected 132 HIV-negative patients as controls. In total, 57.1% of HIV-infected patients had positive sputum smear for AFB compared with 38.6% of controls ( p  = 0.04). Positive culture of pleural fluid was more frequent among the HIV-positive patients than among the controls (63.6% vs. 29.5%, p  = 0.001). There was no significant correlation between CD4 cell count and sputum or pleural fluid results. Mycobacteriological assay was enough for diagnosis in 66.6% of HIV-positive patients compared with 49.2% in controls. After adjusting for other factors and multivariate analysis, HIV remained independently and significantly associated with positive culture of pleural fluid. Conclusion: The diagnostic yield of mycobacteriological studies is higher among HIV-infected patients with pleural TB than among HIV-negative patients. This may decrease the need for pleural biopsy among them. Therefore, a diagnostic approach to pleural TB may be different among HIV-infected patients. In this group of patients, it is prudent to perform sputum and pleural analysis for the detection of AFB before pleural biopsy.